KARAKTERISTIK SEMEN CAIR KALKUN DALAM MEDIA PENGENCER RINGER LAKTAT KUNING TELUR (Characteristics of Turkey’s Liquid Semen in Ringer Lactate Egg Yolk Diluent) - Pamungkas, Ichsan; Rahmi, Annisa; Handarini, Ristika; Baharun, Abdullah (Universitas Nusa Cendana, 2024)
Turkey is a poultry with high economic value, an animal protein resource with high nutrition. Limitations in natural mating cause the small population of turkeys in Indonesia. Therefore, artificial insemination will be a solution to this problem. This research aims to know the diluent effectivity of ringer lactate and egg yolk to preserve turkey’s liquid semen stored at a temperature of 4 °C. The fresh semen from 2 bronze breed turkeys, ages 8 and 12 months, was collected with massage method. This research uses a complete randomized design with four treatment groups for each storage period: T0= storage for 0 hours, T1 = storage for 24 hours, T2 = storage for 48 hours, and T4 = storage for 72 hours with six repetitions for each group. The parameters observed from fresh semen are volume, color, pH, consistency, mass movement, motility, viability, and abnormality. The fresh semen was processed into liquid semen using ringer lactate egg yolk diluent with a ratio of 4:1 and then stored at a temperature of 4 °C. The parameters observed from liquid semen are motility, viability, abnormality, and recovery rate. The data obtained were analyzed using analysis of variance, and in case there were significant differences between treatments, the test was continued with the Duncan test. The results showed that ringer lactate egg yolk diluent can preserve turkey’s liquid semen quality until storage for 48 hours. We can conclude the turkey’s liquid semen in ringer lactate egg yolk diluent can be used for artificial insemination maximum of 48 hours of storage.